Conduction system pacing in the adult congenital population; feasibility and outcomes. (19th May 2022) - Riad, O; Hunnybun, D; O'connor, M; Shi, R; Cantor, E; Jarman, J; Foran, J; Markides, V; Gatzoulis, M; Wong, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left bundle pacing (LBP) is an evolving pacing method designed to capture the intrinsic conduction and minimise ventricular dys- synchrony. Anatomical complexity, scars of previous corrective surgeries and haemodynamic properties of adult congenital heart disease (ACHD) population could increase challenges of LBP. We describe our experience in LBP in ACHD patients and different patient groups. Purpose: To compare the feasibility of LBP in ACHD patient population and non-ACHD patients. Methods: We included all patients who had LBP at our institution in 2020 and 2021. Demographic data, imaging data, procedural parameters and follow up data were collected and analysed. Results: A total of 36 patients were included and divided into two groups: ACHD (n=8, mean age, 54 years, 38% females) and non-ACHD (n=28, mean age, 74 years, 43% females). ACHD anatomy included simple lesions (4) as atrial and ventricular septal defects, partial anomalous pulmonary venous drainage, bicuspid aortic valve and Shone's syndrome, moderate (3), as Tetralogy of Fallot with surgical repair, and complex (1), as transposition of great arteries with Mustard repair. Non-ACHD included patients with structurally normal heart, dilated cardiomyopathy, and those who underwent mitral and aortic valve interventions. Mean left ventricular ejection fraction in ACHD group was 59.5%, and 57.5% in non-ACHD. Late gadolinium enhancement in basal septal area was present in 5 patients in ACHD group. Acute success rate, defined as capture of left bundle branch, was 100% in ACHD group, and 88% in non-ACHD. No acute complications were recorded in both groups. Mean pre-procedural QRS duration was longer in ACHD group (170 ms, vs, 120, p=<0.001). Mean reduction in QRS duration in ACHD group was 27 ms, vs, 15, p= 0.856. Mean procedural and fluoroscopy times were similar in both groups (ACHD, 75.5 minutes, vs, 70, p= 0.26, and ACHD, 9 minutes, vs 7.13, respectively, p= 0.46). Pacing parameters at implantation and after 2 months were satisfactory in both groups (Fig 1). Conclusion: Left bundle pacing is feasible in ACHD population as compared to non-ACHD patients, with low incidence of complications. Procedural and fluoroscopic times were similar in both groups. Pacing parameters were satisfactory and stable over 2 month-follow up.